2021
DOI: 10.1186/s40798-021-00315-9
|View full text |Cite
|
Sign up to set email alerts
|

Modified Talk Test: a Randomized Cross-over Trial Investigating the Comparative Utility of Two “Talk Tests” for Determining Aerobic Training Zones in Overweight and Obese Patients

Abstract: Background To validate the traditional talk test (TTT) and an alternative talk test (ATT; using a visual analog scale) in overweight/obese (OW-OB) patients and to establish its accuracy in determining the aerobic training zones. Methods We recruited 19 subjects aged 34.9 ± 6.7 years, diagnosed with overweight/obesity (BMI 31.8 ± 5.7). Every subject underwent incremental cycloergometric tests for maximal oxygen consumption, and TTT in a randomized o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…target heart rate) could become an obstacle to compliance by individuals (Persinger et al, 2004). Recently, some research demonstrated the consistency of the counting talk test (CTT) (Loose et al, 2012) and the alternative talk test (ATT; using a visual analogue scale) (Orizola‐Cáceres et al, 2021), showing results were accurate and consistent. Hence, subjective methods of exercise training intensity such as the TT and Borg's scale may be more appropriate for exercise during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…target heart rate) could become an obstacle to compliance by individuals (Persinger et al, 2004). Recently, some research demonstrated the consistency of the counting talk test (CTT) (Loose et al, 2012) and the alternative talk test (ATT; using a visual analogue scale) (Orizola‐Cáceres et al, 2021), showing results were accurate and consistent. Hence, subjective methods of exercise training intensity such as the TT and Borg's scale may be more appropriate for exercise during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…23 The TT asks the participants how comfortable they feel speaking during exercise, and its use has been associated with low (≤2 mmol/L; speaking comfortably ), moderate (~3–4 mmol/L; not speaking comfortably ) and high (>5 mmol/L; unable to speak comfortably ) levels of BLa during continuous aerobic type exercise, and has a close relationship with RPE 24 and VT1 or gas exchange threshold. 25 Moreover, the use of the TT can be extended to different populations, including cardiac patients, 26 overweight and obese people 27 and elite athletes, 28 where the use of an analogue scale can strengthen this approach. 27 However, it is important to highlight that the RPE and TT must be approached individually according to the type of exercise prescribed.…”
Section: Aerobic Exercisementioning
confidence: 99%
“…25 Moreover, the use of the TT can be extended to different populations, including cardiac patients, 26 overweight and obese people 27 and elite athletes, 28 where the use of an analogue scale can strengthen this approach. 27 However, it is important to highlight that the RPE and TT must be approached individually according to the type of exercise prescribed. In support of the use of the RPE and TT, recently Bok et al reported that both instruments are reliable and valid measures for the demarcation of ventilatory and lactate thresholds and can be used to elicit homeostatic disturbances associated with moderate, heavy and severe-intensity domains during continuous exercise.…”
Section: Aerobic Exercisementioning
confidence: 99%
“…The application of the TT has been explored since 2002 in different populations, such as athletes [ 13 , 14 , 15 ], men with prostate cancer [ 16 ], overweight and obese patients [ 17 ], and patients with CVD [ 18 ]. It is presently a recommended test in the current guidelines for CVD patients even without a clear definition of the most appropriate protocol [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%